Separation of Coagulation Factors by Means of Starch Gel Electrophoresis - Straub, Werner (Thrombosis and Haemostasis, 1960)
The starch gel electrophoresis method of Smithies was applied to the separation of a concentrate of serum clotting factors. The original hydrolysed potato starch, though forming a suitable gel, was not able to separate clotting factors. They are well separated by using a self hydrolysed maize starch. Different batches of this starch show different separation properties according to the degree of hydrolysis. The factor with the highest mobility, i.e. factor X, is highly purified, while the other factors are purified to a certain extent. The protein content does not exceed 2—3 mg% in a solution containing 100 U/ml of one factor and factor X is 2300 times purer than in plasma. The recovery is much better than in paper electrophoresis and 5—10 times more material can be separated in one experiment.The possibilities of this separation method are limited by the fact that the separated clotting factors are distributed along a distance of only 5—10 cm.